Mediatization of the Net and Internetization of the Print Media in Northern Nigeria - Aondover , Eric Msughter; Umar Maradun, Lawal; M. Yar’Adua, Suleiman (Universitas Islam Indonesia, 2022)
The arrival of new media has generated tensions, arguments and debate about the prospects and future of the newspaper industry all over the world. In Northern Nigeria today, media technologies have led to many changes that are seen in the newspaper industry. For instance, technology has broken distance, making communication easier and the information around the world more accessible; it has shrunk both time and space. This situation has generated debates among scholars, about whether the new media technologies would eventually wipe out the conventional media or at least further redefine them. Within this context, this study aims to examine the Mediatization of the net and Internetization of the print media in Northern Nigeria. The study was anchored on the theoretical lens of Diffusion of Innovation Theory. The study adopted the traditional approach of the positivist research design, which informed the choice of survey method, whereby a self-administered questionnaire in the form of a 4-point Likert scale was used to generate data from the study population of 104 journalists working in the selected newspapers, purposive sampling was used to select the newspapers while simple random sampling was used to select the journalists and IBM® SPSS® Statistics was used to analyse the data. Based on the result, the study discovered that new media technologies posed some challenges like inadequate facilities, epileptic internet availability, and inadequate funds for personnel capacity building to the selected newspapers. The study concludes that the need for newspapers to embrace new technologies in content production and news processing is fundamental for the overall success of the print media in Northern Nigeria.